Adolescent vulnerability to cardiovascular consequences of chronic emotional stress: Review and perspectives for future research - Crestani, Carlos C. [UNESP] (Elsevier B.V., 2017)
Emotional stress has been recognized as a modifiable risk factor for cardiovascular diseases. Adolescence has been proposed as a developmental period of vulnerability to stress. This idea has been mainly supported by experimental research in animals demonstrating a higher impact of chronic emotional stress in adolescents compared with adults. Adolescent vulnerability is also based on evidence that stress during this developmental period affects development, so that enduring changes are found in adult animals that experienced stress during adolescence. The purpose of the present review is to discuss experimental research in rodent models that investigated the impact of long-term exposure to stressful events during adolescence on cardiovascular function. The development of cardiovascular function and autonomic activity in rodents is initially reviewed. Then, a discussion of an adolescent vulnerability to cardiovascular effects of chronic stress is presented. From the reviewed literature, perspective for future research is proposed to better elucidate adolescent vulnerability to cardiovascular complications evoked by chronic emotional stress. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Social stress; Psychological stress; Ontogeny; Adolescence; Cardiovascular function; Autonomic activity; Arterial pressure; Heart rate; Baroreflex; HPA axis; Rodents